TRAF6 Is Required for TRAF2-Dependent CD40 Signal Transduction in Nonhemopoietic Cells - Davies, Clare C. (American Society for Microbiology, 2005)
The emerging role of CD40, a tumor necrosis factor (TNF) receptor family member, in immune regulation, disease pathogenesis, and cancer therapy necessitates the analysis of CD40 signal transduction in a wide range of tissue types. In this study we present evidence that the CD40-interacting proteins TRAF2 and TRAF6 play an important physiological role in CD40 signaling in nonhemopoietic cells. Using mutational analysis of the CD40 cytoplasmic tail, we demonstrate that the specific binding of TRAF2 to CD40 is required for efficient signaling on the NF-κB, Jun N-terminal protein kinase (JNK), and p38 axis. In fibroblasts lacking TRAF2 or in carcinoma cells in which TRAF2 has been depleted by RNA interference, the CD40-mediated activation of NF-κB and JNK is significantly reduced, and the activation of p38 and Akt is severely impaired. Interestingly, whereas the TRAF6-interacting membrane-proximal domain of CD40 has a minor role in signal transduction, studies utilizing TRAF6 knockout fibroblasts and RNA interference in epithelial cells reveal that the CD40-induced activation of NF-κB, JNK, p38, and Akt requires the integrity of TRAF6. Furthermore, we provide evidence that TRAF6 regulates CD40 signal transduction not only through its direct binding to CD40 but also indirectly via its association with TRAF2. These observations provide novel insight into the mechanisms of CD40 signaling and the multiple roles played by TRAF6 in signal transduction.